The Development of a Novel qPCR Assay-Set for Identifying Fecal Contamination Originating from Domestic Fowls and Waterfowl in Israel - Ohad, Shoshanit; Ben-Dor, Shifra; Prilusky, Jaime; Kravitz, Valeria; Dassa, Bareket; Chalifa-Caspi, Vered; Kashi, Yechezkel; Rorman, Efrat (Frontiers in Microbiology, 2016)
The emerging Microbial Source Tracking (MST) methodologies aim to identify fecal contamination originating from domestic and wild animals, and from humans. Avian MST is especially challenging, primarily because the Aves class includes both domesticated and wild species with highly diverse habitats and dietary characteristics. The quest for specific fecal bacterial MST markers can be difficult with respect to attaining sufficient assay sensitivity and specificity. The present study utilizes High Throughput Sequencing (HTS) to screen bacterial 16S rRNA genes from fecal samples collected from both domestic and wild avian species. Operational taxonomic unit (OTU) analysis was then performed, from which sequences were retained for downstream qPCR marker development. Identification of unique avian host DNA sequences, absent in non-avian hosts, was then carried out using a dedicated database of bacterial 16S rRNA gene taken from the Ribosomal Database Project. Six qPCR assays were developed targeting the 16S rRNA gene of Lactobacillus, Gallibacterium, Firmicutes, Fusobacteriaceae and other bacteria. Two assays (Av4143 and Av163) identified most of the avian fecal samples and demonstrated sensitivity values of 91% and 70%, respectively. The Av43 assay only identified droppings from battery hens and poultry, whereas each of the other three assays (Av24, Av13, and Av216) identified waterfowl species with lower sensitivities values. The development of an MST assay-panel, which includes both domestic and wild avian species, expands the currently known MST analysis capabilities for decoding fecal contamination.